Handbook of research on international business and models for global purpose-driven companies - Pérez Uribe, Rafael Ignacio; Largacha-Martinez, Carlos; Ocampo-Guzman, David (Advances in business strategy and competitive advantage., 2021)
"This book includes research describing how international business managers/leaders, both for big and small companies, compete on the global stage while navigating various internal issues as well as the decrease of "hard" management styles in the workforce"--